2013
DOI: 10.1158/1940-6207.capr-13-0121
|View full text |Cite
|
Sign up to set email alerts
|

microRNA Portraits in Human Vulvar Carcinoma

Abstract: Unregulated expression of microRNAs is well known and has already been demonstrated in many tumor types. However, in vulvar carcinoma this field has been unknown territory. Our study characterizes microRNA in vulvar tumors through an expression profile of 754 miRNAs, relating this with clinical and anatomopathologic data, and presence of HPV infection. Twenty HPV-negative and 20 HPV-positive samples, genotyped for high-risk HPVs (HPV16, 18, 31, 33) and a pool of seven normal vulvar skin samples were used for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Nevertheless, many of the miR expression changes detected in HPV16 E6/E7-expressing HFKs were also observed in HPV + head and neck squamous cell carcinoma cell lines (44) and tumors (45). We also observed changes in miR expression that have been detected in HPV + anal carcinomas (46), vulvar cancers (47), and penile squamous cell carcinoma (48). A comparison of our data to miR expression in HPV-associated human biopsy specimens are detailed in Tables S8 and S9.…”
Section: Discussionsupporting
confidence: 53%
“…Nevertheless, many of the miR expression changes detected in HPV16 E6/E7-expressing HFKs were also observed in HPV + head and neck squamous cell carcinoma cell lines (44) and tumors (45). We also observed changes in miR expression that have been detected in HPV + anal carcinomas (46), vulvar cancers (47), and penile squamous cell carcinoma (48). A comparison of our data to miR expression in HPV-associated human biopsy specimens are detailed in Tables S8 and S9.…”
Section: Discussionsupporting
confidence: 53%
“…The first mention of microRNA differential expression in vulvar cancer was provided by our group on a previous study [18] and miR-223-5p appeared as an important microRNA associated with metastasis in HPV negative vulvar samples. In fact, miR-223 arose as a recognized tumor invasiveness and metastasis predictor in several tumor types: its expression was correlated with metastasis in breast [19], gastric [20], colorectal [24] and hepatocellular [25] carcinomas, and osteosarcoma [26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group demonstrated that altered expression of miR-223-5p was associated to the presence of nodal metastasis in patients with vulvar cancer [18]. In fact, this microRNA has emerged as a putative predictor of tumor invasiveness and metastasis, [1921] as well as recurrence [22, 23] in many tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…While miRNA 133a has been suggested as a marker in cardiac disease [29], in most studies it was analyzed in malignant tumors (ovary [30]; vulvar carcinoma [31]; breast [32]). Here, conflicting results were reported, associating miRNA 133a as either a tumor suppressor [30] or a tumor promoter [31]. …”
Section: Discussionmentioning
confidence: 99%